Analysis of Influence Characteristics of Site Conditions on Seismic Response of Utility Tunnel - Konghao Wang; Yuanyuan Chen; Ziyuan Huang; Aiping Tang (Buildings, 2024)
Utility tunnels are crucial infrastructure projects for cities. Earthquakes are a leading cause of damage to these tunnels. The effect of a non-homogeneous site, as a complex site, on the seismic response of utility tunnels cannot be ignored. Therefore, in this study, a non-homogeneous three-dimensional finite element model of a utility tunnel was created using the ABAQUS 2021 software. El Centro seismic waves were inputted while changing the structural depth of burial to investigate the utility tunnel’s seismic response. This research is expected to further clarify the seismic variation in the utility tunnel under complex site conditions. The results show the following: (1) The impact of structure burial depth on the utility tunnel in a non-homogeneous site should not be neglected. The peak acceleration shows a decreasing and then increasing trend with increasing depth of burial within 10 m. Under the same site conditions, the peak accelerations and amplification factors of the soil in the clay are larger than those in the sand. (2) In identical site conditions, the utility tunnel structure experiences larger peak displacements in clay compared to sand. As the structure is buried deeper, the peak displacement of the utility tunnel gradually decreases, while the rate of decrease in the peak displacement of the utility tunnel structure gradually increases. The rate of decrease in peak displacement in clay is greater than that in sand. (3) The stress distribution of the utility tunnel structure changes as the depth of the structure increases. In the clay area, the utility tunnel structure shifts from transverse bending deformation to vertical bending deformation. In the sand area, it maintains transverse bending deformation due to the non-homogeneous site. The findings from this study offer guidance for building utility tunnels on non-homogeneous sites.